Shift in the subgingival microbiome following scaling and root planing in generalized aggressive periodontitis. (6th March 2018) - Liu, Guojing; Luan, Qingxian; Chen, Feng; Chen, Zhibin; Zhang, Qian; Yu, Xiaoqian
Abstract: Aim: To investigate the shift in the subgingival microbiota under scaling and root planing (SRP) in patients with generalized aggressive periodontitis (GAgP). Materials and Methods: After undergoing supragingival scaling, 12 individuals with GAgP were enrolled in this longitudinal study. Full‐mouth SRP was accomplished in 3 weeks and re‐evaluated 6 weeks later. Pooled subgingival samples (posterior‐mesial, posterior‐buccal, anterior‐mesial, and anterior‐buccal) were obtained from each patient before SRP (pre‐treatment group) and at the time of re‐evaluation (post‐treatment group). 16S rRNA PCR products were generated and sequenced after DNA isolation. Results: Under SRP, the diversity of the subgingival community was consistent, whereas genus‐level biomarkers transformed from Porphyromonas, Treponema, and Fretibacterium to Actinomyces, Streptococcus, and Haemophilus . In a network analysis, pathogen‐related and non‐pathogen‐related components were identified in both the pre‐ and post‐treatment groups; the pathogen component was dramatically augmented, while the non‐pathogen component shrank after treatment. Hubs were also distributed in both components pre‐treatment and were confined to the pathogen component post‐treatment. Conclusions: Scaling and root planing decreased periodontal pathogens in the subgingival microbiota of patients with GAgP. However, the shift in the microbiota composition was characterized by the expansion of pathogen‐related components and the contraction of non‐pathogen‐related components 6 weeks after SRP. Clinicaltrials.gov #NCT03090282.